PENGARUH PENERAPAN MODEL PEMBELAJARAN TREFFINGER TERHADAP PENINGKATAN KREATIVITAS BELAJAR SISWA PADA MATERI MENGHIASI PRIBADI DENGAN BERBAIK SANGKA DAN BERAMAL SALEH : Pengaruh Penerapan Model Pembelajaran Treffinger terhadap Peningkatan Kreativitas Belajar Siswa pada Materi Menghiasi Pribadi dengan Berbaik Sangka dan Beramal Saleh - Jannah, Nurusshofi Hamalatil (JEDLISH : Journal Of Education and English Language Teaching, 2023)
The purpose of this research is to find out: (1) the process of applying the treffinger learning model to the material "Adorning Yourself with Kind Thoughts and Virtuous Charity", (2) student learning creativity in the material "Adorning Your Personality with Kindness and Virtuous Charity", (3) The influence of applying the Treffinger learning model on learning creativity in the material "Adorning Your Personality with Kindness and Good Deeds". To prove the hypothesis above, research was carried out using a quasi-experimental method (Quasi Experiment). This research method requires two classes, namely the experimental class and the control class, for the experimental class treatment is given using the Treffinger model, then for the control class it is given using the conventional method. From the research results obtained in the process of implementing this model, the teacher gives group assignments to students, then beforehand the teacher provides stimulation to attract students' attention by playing video shows until they are carried out until the conclusion. As for the learning creativity of students in the experimental class, it can be seen from the average pretest score of 26.54 (26%) and the average posttest score of 42.54 (42%). The research results obtained in the N-gain results for the experimental class obtained a value of 0.71 which is included in the high category, while the percentage for the experimental class was 85%. Therefore, there is an influence of applying the Treffinger learning model on increasing student learning creativity in this material.